Postmenopausal intestinal obstructive endometriosis: case report and review of the literature - Popoutchi, Pedro; Lemos, Carlos Renato dos Reis; Silva, Julio César Rosa e; Nogueira, Antônio Alberto; Feres, Omar; Rocha, José Joaquim Ribeiro da (São Paulo Medical Journal, 2008)
CONTEXT: Endometriosis is characterized by the presence of endometrial tissue outside the uterine cavity, which is commonly detected in gynecological practice but rarely reported as a coloproctological disorder. The objective of the present report was to discuss a rare case of postmenopausal intestinal endometriosis simulating a malignant lesion, following a review of the literature. CASE REPORT: A 74-year-old woman with complaints of hematochezia and tenesmus of two months’ duration accompanied by liquid feces and pelvic pain, but with no other gastrointestinal or gynecological complaints, was referred to our service. She had been menopausal for 22 years, with no hormone replacement treatment, and had undergone panhysterectomy three years before the referral to us, due to endometrial thickening and a right adnexal cyst. Five months before this referral, she had undergone laparotomy due to acute obstructive abdomen, which revealed a tumor mass involving the small bowel. Anatomopathological examination of the enterectomy suggested a hypothesis of intestinal endometriosis. A proctological examination was normal. Computed tomography of the pelvis revealed thickening of the rectosigmoid transition and colonoscopy revealed friable tumor formation in the rectum. A biopsy of the lesion revealed mucosal fragments of endometrial type, which led to a review of the previous anatomopathological examination. The patient underwent rectosigmoidectomy with protective transversotomy, with a good postoperative course, and anatomical examination confi rmed the intestinal endometriosis. The patient subsequently suffered a stenosing recurrence of the lesion and has undergone colostomy since then.